Thermal properties of modified carbon films. Issue 1 (1st February 2016) - Kalenik, Jerzy; Kielbasinski, Konrad; Firek, Piotr; Czerwosz, Elżbieta; Szmidt, Jan
Abstract : Purpose: – The purpose of this paper is to present thermal properties of palladium-carbon films prepared by physical vapour deposition (PVD)/chemical vapour deposition (CVD) methods. Design/methodology/approach: – Thin palladium-carbon films were prepared at Tele- and Radioresearch Institute. Test structures containing palladium-carbon films and titanium electrodes were made. Temperature-resistance characteristics were measured. Findings: – The results show strong temperature dependence of modified carbon film resistance. The dependence is stable, and so modified carbon films can be applied for various electronic applications. Originality/value: – The paper presents thermal properties of thin palladium-carbon prepared by original PVD/CVD method at Tele- and Radioresearch Institute.